The Distance between Tibial Tubercle and Trochlear Groove Correlates with Knee Articular Torsion - Barahona, Maximiliano; Guzmán, Mauricio; Barrientos, Cristian; Zamorano, Álvaro; Palet, Miguel; Hinzpeter, Jaime; Collaborating Authors; Sato, Yoshiro; Catalan, Jaime; Infante, Carlos; Garrido, Cristian (The Journal of Knee Surgery, 2020)
This study aims to correlate the tibial tubercle to trochlear groove (TT-TG) distance with knee axial alignment. The hypothesis is that as internal torsion of the distal femur or external torsion of the proximal tibial increases, the TT-TG distance increases. We designed a cross-sectional study approved by our institutional ethics review board. We reviewed 32 computed tomography angiographies of patients that have nonjoint or bone-related symptoms. Distal femoral torsion, proximal tibial torsion, knee articular torsion (AT), and TT-TG distance were measured. A regression analysis between the TT-TG distance and the AT was performed. A positive correlation between the TT-TG distance and the AT was found. An increase in external torsion of the proximal tibial or an increase in internal torsion of the distal femur increases the TT-TG distance. For a correct interpretation of the TT to trochlear groove distance, we propose that the axial alignment should be included in the regular analysis of patellofemoral disease.
Keywords: tibial tubercle to trochlea groove distance; patellofemoral pain; patellar instability; articular torsion